1991
DOI: 10.1007/bf00572699
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and assimilative enzyme activities in continuous cultures of the obligate methylotrophMethylobacillus flagellatum

Abstract: In methanol-limited continuous cultures of the obligate methylotrophic bacterium Methylobacillus flagellatum grown at rates from 0.05 to 0.63 h-1, and also in an oxyturbidostat culture of M. flagellatum growing at the rate of 0.73 h-1, levels of methanol dehydrogenase, enzymes of formaldehyde oxidation (both linear and cyclic) and assimilation (RuMP cycle), a number of intermediary metabolism and TCA cycle enzymes and also 'dye-linked' formaldehyde dehydrogenase were determined. It was shown that the activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, while high activities for the enzymes of the H 4 MPT pathway have been measured, mutants in these enzymes revealed only very subtle phenotypes, suggesting a minor role in formaldehyde oxidation. Formate dehydrogenase activity was reported only in cells of M. flagellatus (and other RuMP methylotrophs) when grown in a chemostat at low dilution rates (6,12,13), consistent with the nonessential role of the linear pathway. However, here we detected all the components of the linear pathway, including the two alternative formate dehydrogenases.…”
Section: Resultsmentioning
confidence: 72%
“…However, while high activities for the enzymes of the H 4 MPT pathway have been measured, mutants in these enzymes revealed only very subtle phenotypes, suggesting a minor role in formaldehyde oxidation. Formate dehydrogenase activity was reported only in cells of M. flagellatus (and other RuMP methylotrophs) when grown in a chemostat at low dilution rates (6,12,13), consistent with the nonessential role of the linear pathway. However, here we detected all the components of the linear pathway, including the two alternative formate dehydrogenases.…”
Section: Resultsmentioning
confidence: 72%
“…(i) Primary oxidation of methanol and methylamine. M. flagellatus exhibits high growth rates on methanol or methylamine (up to 0.73 h Ϫ1 [2,3,7]) and possesses high activities of MDH and MADH, respectively (7,37). The genome analysis revealed the presence of a gene cluster predicted to encode MDH and accessory proteins (mxaFJGIR SACKLD; Mfla2034 to Mfla2044) similar to the clusters characterized in other methylotrophs (9,52,54).…”
Section: Resultsmentioning
confidence: 88%
“…The major metabolic modules involved in methylotrophy in M. flagellatus, as described above, include oxidation systems for methanol and methylamine, the RuMP cycle for formaldehyde oxidation that overlaps to a large degree with the assimilatory RuMP cycle, and the H 4 MPT-linked formaldehyde oxidation pathway. While at least one putative formate dehydrogenase is encoded in the genome, its contribution to methylotrophy is predicted to be minor, based on the previous experiments demonstrating low levels of FDH activity during growth on C 1 compounds and the predominant role of cyclic oxidation of formaldehyde that does not involve formate as an intermediate (7,37). In terms of primary C 1 oxidation functions, genome comparisons revealed that gene clusters encoding the methanol dehydrogenase function in M. flagellatus were similar to those of the respective gene clusters in M. extorquens and M. capsulatus (9, 54), while no major methanol oxidation cluster encoding the large and the small subunits of MDH and an associated cytochrome (MxaG) were identified in M. petroleiphilum (34).…”
Section: Vol 189 2007 Genome Of Methylobacillus Flagellatus 4023mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple potential pathways for formaldehyde oxidation are also present in the obligate RMP pathway methylotroph Methylobacillus flagellatus KT (a β-proteobacterium). Two possibilities, the direct oxidation by a NAD-linked formaldehyde dehydrogenase, and oxidation by a ' dye-linked ' periplasmic formaldehyde dehydrogenase, seem unlikely to be major dissimilatory routes, due to the low activities of these enzymes in the cells (Kletsova et al, 1987 ;Chistoserdova et al, 1991). However, the other two pathways, the cyclic oxidation via 6-phosphogluconate dehydrogenase and the linear oxidation via H % MPT derivatives, involve much higher enzyme activities and each could be important for methylotrophic growth (Kletsova et al, 1987 ;Vorholt et al, 1999).…”
Section: Discussionmentioning
confidence: 99%